Transcortical anesthesia in simple and complex tooth extractions (Research, Society and Development, 2020)
Transcortical anesthesia consists of depositing the anesthetic solution in the cancellous bone adjacent to the tooth to be anesthetized. The objective of this work is to present a retrospective scientific survey on the clinical efficacy of transcortical anesthesia applied to simple and complex extractions through a literature review. A search was carried out on the bases Pubmed, SciELO and Scopus, using as models of keywords "intraosseous injection AND oral surgery", "dental extraction AND intraosseous anesthesia", "mandibular third molar surgery AND intraosseous injection" and “tooth extraction AND transcortical anesthesia”. Clinical studies published between 2000 and 2020 in English were included. Laboratory studies, studies in animals, clinical cases and reports of literature were excluded. As for the results, 92 were included using keywords, 7 of which were included after inclusion and exclusion criteria, by reading the titles, abstracts and full texts. The majority (n = 6) were clinical studies, of which 5 were randomized. All studies evaluated the QuickSleeper system, including comparison of transcortical anesthesia with the lower alveolar nerve block technique (n = 3). Pain perception (n = 3) and effectiveness (n=4) were the most recurrent factors in the studies. The transcortical anesthesia is an alternative to conventional techniques and can be applied in cases of failure or insufficiency of conventional anesthesia in simple and complex extractions.